A Constant Rank Constraint Qualification in Continuous-Time Nonlinear Programming - do Monte, Moisés Rodrigues Cirilo; de Oliveira, Valeriano Antunes [UNESP] (Springer Nature, 2020)
The paper addresses continuous-time nonlinear programming problems with equality and inequality constraints. First and second order necessary optimality conditions are obtained under a constant rank type constraint qualification. The first order necessary conditions are of Karush-Kuhn-Tucker type.
Keywords: Constant rank condition; Constraint qualifications; Continuous-time programming; Necessary optimality conditions; Nonlinear programming